Peningkatan keterampilan dan pendapatan ibu-ibu Dasawisma dan Karang Taruna melalui kerajinan pengolahan barang sisa - Agustina, Yenni; Indra, Ahmad Zubaidi; Nirmala, Tiara; Widiyanti, Ade (Yumary: Jurnal Pengabdian kepada Masyarakat, 2020)
Purpose: Housewives and young people have the potential to support the household economy. Tanjung Raya is one of the families located in the sub-district of Peace in Bandar Lampung. Based on statistical data, the majority of jobs in this sub-district are laborers, of course, this is sad when the location is strategic for conducting business activities, but not many people have used it. The weakness experienced by these residents is the lack of skills so that to overcome this the PkM team took the initiative to carry out activities to increase the skills and income of participant, Tanjung Raya Village in the field of handicraft processing of used goods, especially used cooking oil. This activity is specifically aimed at improving the skills and knowledge of participants. Method: This PkM activity collaborates with the Nabbay Hanggum community who act as a resource for this activity. Results: The result of this activity is an increase in the skills of the participants so that it can be concluded that this activity has a positive impact. Conclusion: This activity has a positive impact on increasing the skills and income of the participant group. Keywords: Skills, Used oil, Income